A network system for vitellogenin synthesis in the mussel Mytilus galloprovincialis (L.). Issue 3 (23rd November 2012) - Agnese, Marisa; Verderame, Mariailaria; De Meo, Enrico; Prisco, Marina; Rosati, Luigi; Limatola, Ermelinda; del Gaudio, Rosanna; Aceto, Serena; Andreuccetti, Piero
Abstract The aim of this study is to assess, by RT‐PCR, in situ hybridization, electron microscopy, and immunohistochemistry, the site/s of vitellogenin (VTG) synthesis in the mussel Mytilus galloprovincialis. Our investigations demonstrate that, among the analyzed tissues, the synthesis of VTG occurs only in the female gonad, that is, within the oocyte and follicle and connective cells. Such a synthesis is just evident in early vitellogenic oocytes, whose cytoplasm is characterized by numerous RER cisternae and an extended Golgi complex surrounded by nascent yolk platelets. The synthesis of VTG goes on in vitellogenic oocytes assuming a pear form, and progressively reduces once the oocyte shows the pear or polygonal form, typical of those oocytes that have concluded the growth. The expression of VTG occurs also within follicle (auxiliary) and connective cells. In particular, it is noteworthy that follicle cells are characterized by numerous RER cisternae and an active Golgi complex surrounded by numerous vesicles and vacuoles containing electron dense material. The same material is also present along their plasma membrane, within the intercellular space between oocyte and follicle cells, and finally within invaginations of the oocyte surface, thus suggesting a VTG transfer to the oocyte via endocytosis. Differently, no VTG synthesis was observed within digestive gland. All together the findings here reported strongly suggest that in M. galloprovincialis, inside the gonad, the VTG synthesis occurs in the oocyte (autosynthesis) and in the follicle and adipogranular cells (heterosynthesis). J. Cell. Physiol. 228: 547–555, 2013. © 2012 Wiley Periodicals, Inc.